O dólmen 2 de chão redondo (Sever do Vouga, Aveiro): um monumento com iconografias. Resultados dos trabalhos de escavação e restauro - Santos, Filipe; Coutinho, Luís; Perpétuo, João; Santos, André (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
We present the results concerning the archaeological work carried on on Monument 2, in Chão Redondo (Sever do Vouga, Aveiro, Portugal), by the responsibility of ARQUEOHOJE company. The foregoing mentioned dolmen, presents quite conventional (classical) characteristics, with chamber and hall way different in layout and hoist. Engravings can be seen on some of their orthostats. This recent intervention is quite important, firstly because it was possible to define, in a satisfactory way, the whole set of processes and techniques used for the erecting and subsequent sealing off of this tomb. Secondly, a frontier-limit of the monument was settled, with areas for the rituals and accesses to its interior, imbued with a symbolic meaning rather than a functional one. Concerning the most recent data and studies, the rock engravings on the orthostats, which are part of the chamber and hallway of the monument, are re-visited.